ANALISIS PENGGUNAAN FITUR SHOPEE PAYLATER DALAM PERSPEKTIF MAHASISWA PERBANKAN SYARIAH FEBI UIN STS JAMBI - Salsadila Habiba; Sissah Sissah; Erwin Saputra Siregar (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This study aims to Analyze the Use of the Shopee PayLater Feature from the perspective of Islamic banking students at FEBI UIN STS Jambi. Shopee PayLater is one of the payment features that allows users to buy now and pay later with or without installments. This study uses a qualitative approach with a descriptive method, where data is collected through in-depth interviews with students who actively use the Shopee PayLater feature. The results obtained through findings and research can be concluded. The use of the Shopee PayLater Feature by Students causes increased spending and debt in the future, which can ultimately harm their personal finances if not managed properly after they use Shopee PayLater. This is proven by as many as 70% of informants consuming goods or services continuously exceeding their actual needs without seeing whether the goods or services consumed have benefits that are only used for social status.Positive and Negative Impacts of Using the Shopee PayLater Feature due to several aspects, namely. Positive Impact: Reducing Stress, Keeping Up with the Times, Increasing Self-Confidence. Negative Impacts: Wasteful, Addiction to excessive shopping, Risks if not in accordance with income, interest rates that continue to rise, many victims are trapped. Also, the Reasons Why Students Misuse the Use of the Shopee PayLater Feature The reason why students often misuse the use of Paylater is due to excessive use of Paylater, use of limits that are not in accordance with certain rules and are often tempted by discounts & promos given so that they have not been able to apply, namely the suitability between consumption and income.